The Yoruba version of LittlEARS auditory questionnaire: evaluation of auditory development in children with normal hearing (2018)
The goal of this study was to translate the LittlEARS Auditory Questionnaire into Yoruba language for use with Yoruba-speaking parents and to evaluate the psychometric properties of the Yoruba version of questionnaire. Translation of the LittlEARS Auditory Questionnaire into Yoruba language was done using a back-translation method. The study participants included 423 parents of normal hearing children aged 6e24 months. Psychometric analyses (scale analysis and item analysis) of the translated questionnaire was done. The scale characteristics in the dataset are: Internal consistency: Cronbach's alpha ¼ 0.907; reliability; Split-half ¼ 0.701; predictive accuracy; Guttman's lambda ¼ 0.583; correlation between total score and children's age¼ 0.783. The regression analysis showed that 75.3% of the variance in the total scores can be explained by age. The Yoruba version of the LittlEARS Auditory Questionnaire is a dependable and valid tool as evidenced by the results of psychometric analyses. The tool is useful for assessing auditory development in children between 6 and 24 months of age